OBSERVATIONS ON OCCURRENCE AND IDENTITY OF POWDERY MILDEW OF CUCURBlTS IN TAMIL NADU - M. WAJID KHAN, G. K. SHARMA and (Indian Phytopathology, 2002)
This study considered the occurrence of powdery mildew on cucurbits in Tamil Nadu and determined the identity of the causal species of the disease in the State. Most of the cucurbits were infected in one or the other locality in the study area of the State which comprised 3 districts and localities in and around Madras city. Bottlegourd, Lagenaria siceraria, was most severely affected crop. Watermelon, Citrullus ianatus, was conspicuous in being disease- free in all the localities surveyed. A wild cucurbit, Coccinia grandis was also infected. Teleomorph of the pathogens(s) causing the disease were found on L. siceraria and C. grandis. Utilizing anamorph and teleomorph characters, the species responsible for the disease in the State were identified as Sphaerotheca juiiginea and Erysiphe cichoracearum. S. fuiiginea was widespread causing the disease on all the cultivated cucurbits. E. cichoracearum was confined to C. grandis. The identity situation of the species causing the disease and their pathogenicity spectrum in the State are similar to several other states in India.